Apical periodontitis: preliminary assessment of microbiota by 16S rRNA high throughput amplicon target sequencing - Federico Mussano; Ilario Ferrocino; Natalija Gavrilova; Tullio Genova; Alessandro Dell'Acqua; Luca Cocolin; Stefano Carossa (BMC, 2018)
Abstract Background Apical periodontitis includes periapical granulomas and radicular cysts, which are histologically distinguished by the absence and the presence of an epithelial lining, respectively. The main cause of apical periodontitis is the bacterial colonization of the root canal space. This research aimed at assessing whether and how periapical granulomas and radicular cysts differ in terms of microbiota using high throughput amplicon target sequencing (HTS) techniques. Methods This study included 5 cases of Periapical Granulomas (PGs) and 5 cases of Radicular Cysts (RCs) selected on the base of histology out of 37 patients from January 2015 to February 2016. Complete medical history, panoramic radiograms (OPTs) and histologic records of each patient were assessed. Only lesions greater than 1 cm in diameter and developed in proximity to teeth with bad prognosis were included. The microbiota present in periapical granulomas and radicular cysts thus retrieved was finely characterized by pyrosequencing of the 16S rRNA genes. Results The core of OTUs shared between periapical granulomas and radicular cysts was dominated by the presence of facultative anaerobes taxa such as: Lactococcus lactis, Propionibacterium acnes, Staphylococcus warneri, Acinetobacter johnsonii and Gemellales. L. lactis, the main OTUs of the entire datasets, was associated with periapical granuloma samples. Consistently with literature, the anaerobic taxa detected were most abundant in radicular cyst samples. Indeed, a higher abundance of presumptive predicted metabolic pathways related to Lipopolysaccharide biosynthesis was found in radicular cyst samples. Conclusions The present pilot study confirmed the different microbial characterization of the two main apical periodontitis types and shade light on the possible role of L. lactis in periapical granulomas.